¿Desde dónde se mide la marginación? Una observación a los indicadores absolutos de exclusión del Consejo Nacional de Población en México - Andrea Aguilar Edwards (Comparative Cultural Studies, 2016)
This paper focuses synthetically addressing some key aspects that add to itself -and serious- structural problems of political, economic and social order, creating conditions that exacerbate the marginalization from symbolic interaction in a society, either, but here it is the Mexican case addresses. The first part is theoretically analyzed the concepts of identity, culture and civilization, as generators of some of the conditions which, naturally, trigger processes of marginalization and social exclusion. This reflection becomes the framework that allows, in the second part of this work, a general review of the conceptual scheme of marginalization in Mexico, from the indicators that the National Population Council defined to measure rates marginalization in the country. Some final considerations point to the low relevance of these indicators and their inconsistency to support a report on the conditions of marginalization that even comes close to reality that exists in Mexico.